ANALYSIS OF THE SOURCES OF PROVISION OF FUNDING IN THE SPORT SYSTEM IN BULGARIA - Tsankov, Tsanko (Revista Inclusiones, 2020)
Sports development and management is a complex social and economic system. This requires the setting of new requirements for the improvement of these systems and an adequate systematic approach in line with the economic, social, technological, technical and scientific changes on a worldwide scale. The resource provision of the sports system in Bulgaria must also be adequately complied to, and in line with these new socio-economic conditions. Studying the application of the existing program-project approach and its efficiency for the achievement of high sports achievements, is the aim of the present research. Based on the analysis of the existing system for resource provision of elite sports, and the extremely rapidly changing socio-economic conditions, it is necessary to implement more shorter-term strategies for more effective implementation, organization and management of the elite sports in Bulgaria.